EVALUASI POTENSI SUMBERDAYA AIR SUNGAI UNTUK PENGAIRAN DI PROVINSI JAWA BARAT DAN BANTEN - Purnama, Ig. Setyawan (BPPT)
The objectives of this research are to calculate river water potency and irrigation need in West Java and Banten, and evaluate its water balance. Calculation of river water potency is based on river discharge data in each river basins, whereas calculation of water need for agriculture is based on area width and irrigation need. The result of the research shows that the highest river water potency in West Java is in Cisadane-Ciliwung River Basins about 3119.81 million m3/year. The lowest river water potency is in downstream Citarum River Basin about 383.55 million m3/year. In Banten, the highest river water potency is in Cisadeg-Cikuningan River Basins about 4476.32 million m3/year, whereas thelowest is in Labuhan Merak River Basin about 596.33 million m3/year. According to water balance evaluation, the water balance of two provinces are also variative. In West Java, Upstream Citarum River Basin and Downstream Citarum River Basin almost get water defi cit in along year. In Banten, water defi cit in river basins just happen in several month. Base on water surplus, there are no river basin in West Java that get water surplus along year. In Banten, Ciujung River Basin get water surplus along year.Key words : river water, irrigation, river basin